Rationale For Simultaneous Pulpectomy for Prostate Cancer - Allazov Salakh Allazovich; Giyasov Shukhrat Iskandarovih; Ishmuradov Bahron Tursunovich; Batirov Bexzod Aminjanovich; Negmatov Komiljon Nozim ugli (Zien Journals, 2022)
The article is devoted to the problem of using the median incision along the Veslingline for simultaneous performance of surgery on the organs of both halves of the scrotum (- 8 etc.). The results of simultaneous operations on the scrotum organs in 32 patients indicate the cosmetic advantages of this skin incision and prompt access, the efficiency of the surgical material and the duration of the operation itself.
Keywords: Prostate cancer; Wesling’s line; simultantpulpectomy; patients